(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this study was to investigate the hypothesis that there is a correlation between the parenting styles that adolescents are exposed to and their academic achievement. In addition, the purpose of the study was to evaluate the impact that the gender of teenagers had on their academic performance. The sample included two hundred young people who were enrolled in academic programs ranging from intermediate to post-graduate levels in the Darbhanga district of Bihar, India. The participants were chosen through the use of a sample strategy known as purposive-cum-incidental sampling. The researchers determined the academic accomplishment of the individuals by totalling up all of the marks they had received over the previous three years. The Adolescent Parenting Attitude Four Factor Questionnaire was utilised to assess the various parenting approaches by adolescents. On this scale, which was designed by Shyny (2017), four different parenting styles are measured. One of the findings of the study was that there was no significant correlation between the parenting styles that adolescents were exposed to and their academic success. A further observation was that there was no discernible impact of gender on the academic performance of teenagers